PENINGKATAN KESADARAN MASYARAKAT MELALUI PENYULUHAN HUKUM TENTANG IZIN USAHA PERDAGANGAN DI DESA GIRI MADIA, KECAMATAN LINGSAR, KABUPATEN LOMBOK BARAT - I GUSTI AGUNG WISUDAWAN; BUDI SUTRISNO; DIMAN ADE MULADA; L. ACHMAD FATHONI (Universitas Mahasaraswati K. Mataram, 2023)
This paper focuses on increasing public awareness about the importance of obtaining a trading business license in Giri Madia Village, Lingsar District, West Lombok Regency. The formulation of the problem in this paper is what are the benefits of administering a trading business license and what is the mechanism for obtaining a trading business license. The type of research used in this study is Normative-Empirical Research with Statute Approach, Conceptual Approach and Sociological Approach. This paper uses legal materials consisting of primary legal materials, namely Law No. 20 of 2008 concerning Micro, Small and Medium Enterprises,Regulation of the Minister of Trade of the Republic of Indonesia No. 07/M-Dag/PER/2/ 2017 Regarding the Third Amendment to the Regulation of the Minister of Trade Number 36/M-Dag/PER/9/2007 concerning Issuance of Trading Business Permits and Regulation of the Minister of Trade of the Republic of Indonesia No. 50 of 2020 concerning Provisions for Business Licenses, Advertising, Guidance and Supervision of Business Actors in Trade Through Electronic Systems. Secondary Legal Materials, namely literature and scientific articles relating to the issues raised in this study and Tertiary Legal Materials consisting of legal dictionaries and encyclopedias. The technique of collecting legal material/data used in this study is Documentation Studies and Interviews with Analysis of Legal Materials, namely Qualitative Descriptive Analysis with deductive conclusions. The results of this study are that the people of Giri Madia Village have increased their understanding and enthusiasm for managing trade business permits in running a business either directly or through E-Commerce. Apart from that, the benefits of having a business license are opening up access for MSME actors to obtain credit at financial institutions.